KORELASI MINAT BACA DENGAN KEMAMPUAN MENULIS KARANGAN NARASI BAHASA INDONESIA KELAS V SEKOLAH DASAR - Setiawan, Fanny; Syamsiati, Syamsiati; Sugiono, Sugiono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze whether there is a correlation between reading interest with essay writing narrative skills Indonesian of fifth grade students Elementary School 08 Sungai Kakap.This research uses descriptive method with research form correlation study. The population in this study were all students of class V Elementary School School 08 Sungai Kakap consisting of two classes, is V A and V B amounted to 67 students.Based on the analysis of students' reading interest overall 6871 or with the percentage of 85.56% and the results of analysis of essay writing narrative skills overall for 4775 with an average of 71.26. The result of calculation of correlation coefficient is known that r_(xy) is 0,380 while r _tabel with significant level 5% for N = 67 and db (degrees of freedom) = N-2 = 67-2 = 65 is 0,244. Thus r_(xy)> r_(table) or 0.380> 0.244. Thus, it can be concluded that there is a correlation between reading interest with essay writing narrative skill.Keywords :Riding interest and composition, Essay writing narrative skill